Detection of submillisecond spike timing differences based on delay-line anticoincidence detection - Lyons-Warren, Ariel M. (American Physiological Society, 2013)
Detection of submillisecond interaural timing differences is the basis for sound localization in reptiles, birds, and mammals. Although comparative studies reveal that different neural circuits underlie this ability, they also highlight common solutions to an inherent challenge: processing information on timescales shorter than an action potential. Discrimination of small timing differences is also important for species recognition during communication among mormyrid electric fishes. These fishes generate a species-specific electric organ discharge (EOD) that is encoded into submillisecond-to-millisecond timing differences between receptors. Small, adendritic neurons (small cells) in the midbrain are thought to analyze EOD waveform by comparing these differences in spike timing, but direct recordings from small cells have been technically challenging. In the present study we use a fluorescent labeling technique to obtain visually guided extracellular recordings from individual small cell axons. We demonstrate that small cells receive 1–2 excitatory inputs from 1 or more receptive fields with latencies that vary by over 10 ms. This wide range of excitatory latencies is likely due to axonal delay lines, as suggested by a previous anatomic study. We also show that inhibition of small cells from a calyx synapse shapes stimulus responses in two ways: through tonic inhibition that reduces spontaneous activity and through precisely timed, stimulus-driven, feed-forward inhibition. Our results reveal a novel delay-line anticoincidence detection mechanism for processing submillisecond timing differences, in which excitatory delay lines and precisely timed inhibition convert a temporal code into a population code.